The regression of endometriosis with glycosylated flavonoids isolated from Melilotus officinalis (L.) Pall. in an endometriosis rat model - Mert Ilhan; Zulfiqar Ali; Ikhlas A. Khan; Hakkı Taştan; Esra Küpeli Akkol (Elsevier, 2020)
Objective: Melilotus officinalis (L.) Pall. is commonly used for treating bronchitis, painful menstruation, hemorrhoids, kidney stones, ulcers of the eyes, earache, and hardening and swelling of uterus. The European Medicines Agency reported the use of M. officinalis orally against stomach ache, gastric ulcer, and disorders of the liver and uterus in folk medicine. The present study aimed to appraise the activity of M. (L.) Pall. aerial parts in endometriosis rat model. Materials and methods: The endometriosis rat model was used to evaluate the potential activity of M. officinalis aerial parts based on its folkloric usage. The aerial parts of M. officinalis were extracted with n-hexane, ethyl acetate (EtOAc), and methanol (MeOH), respectively. The adhesion scores, endometrial foci areas, and cytokine levels were measured in all treated groups. After the biological activity studies, phytochemical studies were performed on the active extract and the fractions obtained from the active extract. Results: The MeOH extract significantly decreased the endometrial foci areas and cytokine levels in rats with endometriosis. Fractionation was performed on the MeOH extract to achieve bioactive molecules. Following the fractionation, the fractions obtained from the MeOH extract were tested. Fraction C showed the highest activity in the rat endometriosis model. Phytochemical investigation of the active fraction (Fraction C) resulted in isolation and elucidation of some quercetin and kaempferol glucoside derivatives. Conclusion: Fraction C obtained from the MeOH extract of M. officinalis showed the highest activity, yielding four glycosylated flavonoids. Keywords: Endometriosis, Glycosylated flavonoids, Fabaceae, Melilotus officinalis, Rat